(untitled) - Stein, Theodore J (New York, 1998)
Includes bibliographical references (p. 227-246) and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: AIDS (Disease) in women -- Patients -- Legal status, laws, etc. -- United States; Children of AIDS patients -- Legal status, laws, etc. -- United States; HIV-positive women -- Legal status, laws, etc. -- United States; Women patients -- Services for -- United States; Social welfare -- United States; Women -- HIV (AIDS) -- Legal protections; Phúc lợi xã hội -- Hoa Kỳ; Phụ nữ -- HIV (AIDS) -- Bảo vệ pháp lý; Children -- HIV (AIDS) -- Legal protections; Trẻ em -- HIV (AIDS) -- Bảo vệ pháp lý